Iraq Investment Climate Assessment 2012 - World Bank (World Bank, Washington, DC, 2017)
Despite decades of war and instability, Iraq's abundant natural resources, strategic geographic location and cultural history endow Iraq with tremendous potential for growth and diverse economic development. Driven by windfall oil revenues in recent years, the Government of Iraq has invested heavily in rebuilding the infrastructure of the country, and its abundant oil reserves ensure that progress can continue steadily. This report was initiated at the request of the Iraqi government to assess the local investment climate and identify those high priority factors which most significantly impede private sector development in Iraq, in an effort to prioritize the recommended investments, institutional and regulatory reforms which would most significantly contribute to sustainable private sector growth and increased productivity.